Aerobic biofilm providing a habitat for anammox bacterial survival in mainstream of municipal wastewater treatment plants. (February 2022) - Lv, Kai; Peng, Dangcong; Han, Yun; Yu, Lifang
Abstract: Enrichment and accumulation of anaerobic ammonium oxidation (anammox) bacteria is a key to success in anammox-based nitrogen removal in mainstream in municipal wastewater treatment plants (WWTPs). In this study, relatively high percentage of anammox bacteria was detected in biofilm employed in aerobic zone of two WWTPs (one with Orbal Oxidation ditch process, and the other with anaerobic-anoxic-oxic (A 2 /O) process) in Xi'an, China. The high-throughput sequencing results showed that Ca. Brocadia responsible for nitrogen removal detected with relative abundance of 0.95 ± 0.21% (Orbal Oxidation ditch) and 0.71 ± 0.14% (A 2 /O) of the total bacteria in biofilm. The anammox activities could be estimated to be 5.98 ± 1.32 mg NH4 + -N/g VSS/d (Orbal oxidation ditch) and 1.36 ± 0.25 mg NH4 + -N/g VSS/d (A 2 /O) after short-term precultivation. The contribution to nitrogen removal by anammox process were 2.49 ± 0.87% (Orbal oxidation ditch) and 2.89 ± 2.06% (A 2 /O) through mass balance calculation. In addition, enhanced batch test demonstrated that partial-nitritation process might play an important role in anammox enrichment but need further research. Overall, this study suggested that aerobic biofilm (AB) might be a candidate to enhance nitrogen removal in mainstream. Graphical abstract: Unlabelled Image Highlights: High percentage of anammox were detected in aerobic biofilm taken from WWTPs. Aerobic biofilm show appreciable anammox activities after precultivation. Partial-nitritation (PN) process might improve anammox enrichment in mainstream.